Risk Factors Associated with Fall Awareness, Falls, and Quality of Life Among Ethnic Minority Older Adults in Upper Northern Thailand - Kantow S (Dove Medical Press, 2021)
Supakan Kantow,1 Katekaew Seangpraw,1 Parichat Ong-artborirak,2 Prakasit Tonchoy,1 Nisarat Auttama,1 Sasivimol Bootsikeaw,1 Monchanok Choowanthanapakorn1 1School of Public Health, University of Phayao, Phayao, 56000, Thailand; 2Faculty of Public Health, Chiang Mai University, Chiang Mai, 50200, ThailandCorrespondence: Katekaew SeangprawSchool of Public Health, University of Phayao, Phayao, 56000, ThailandTel +66 54 466 66Email eungkaew@gmail.comBackground: Falls are a major public health issue and one of the leading causes of morbidity and mortality among the older adults in many countries. Falls and their consequences have an impact on people’s quality of life, particularly the older adults. However, there have been very few studies on falls among ethnic minority groups living in rural areas. The aim of this study was to examine factors related to fall awareness, falls, and quality of life among ethnic minority older adults living in northern Thailand.Methods: A cross-sectional study was conducted among 462 older adults from ethnic minority groups living in rural communities in Phayao and Lamphun provinces of northern Thailand using a multi-stage sampling technique. The data were collected through face-to-face interviews, with structured questionnaires covering health information, fall awareness, and quality of life (WHOQOL-OLD). The factors were determined using simple linear regression and binary logistic regression.Results: The mean age of the participants was 68.2, Karen (35.5%), Mien (24.2%), indigenous (20.8%), and Hmong (19.5%). In the previous 12 months, 20.6% of elders had experienced a fall, and 4.5% of them had experienced multiple falls. More than half of the elders had moderate fall awareness and quality of life (71.6% and 68.6%, respectively). Univariate analysis revealed that minority group, sociodemographic characteristics, sleep duration, and fear of falling were all found to be associated with fall awareness, falls, and quality of life score (p< 0.001). There was a significant relationship among fall awareness, falls, and quality of life score (p< 0.001). Compared to those who had not fallen in the previous year, the quality of life of the older adults who had fallen was about 11 points lower.Conclusion: Several independent variables were discovered to be fall risk factors and quality of life indicators. It is critical to recognize the risk factors to promote fall prevention programs that are appropriate for the older adults among ethnic minorities. Therefore, public health agencies and local government should be aware of the problem and initiate an implementation program and policy to prevent falls and improve the quality of life among ethnic minority older adults.Keywords: fall awareness, falls, quality of life, older adults, ethnic minority